Immunogenicity and safety of a liquid Pentavalent (DTwP-Hb-Hib) combination vaccine manufactured by Human Biologicals Institute in 6–8 weeks old healthy infants: A phase III, randomized, single blind, non-inferiority study. Issue 36 (23rd August 2019) - Susarla, Sai Krishna; Gupta, Madhu; Mantan, Mukta; Dhongade, Ramchandra; Bhave, Sheila; Das, Rajat Kumar; Ray, Rajib Kumar; Ramesh Babu, T.; Ravi, M.D.; Krishnamurthy, B.; James, Saji; Sandhya, G.; et al.
Abstract: Background: A liquid Pentavalent (DTwP-Hb-Hib) combination vaccine, developed by Human Biologicals Institute, underwent a Phase III clinical study in India. In this randomized, single blind, non-inferiority study, the immunogenicity and safety of this Investigational vaccine was compared with Pentavac SD® vaccine in 6–8 weeks old healthy infants. Methods: A total of 405 healthy infants aged 6–8 weeks old were randomized in 2:1 ratio to receive three doses of either the Investigational liquid Pentavalent (DTwP-Hb-Hib) combination vaccine or Pentavac SD® vaccine at four to six weeks interval. Immunogenicity was compared by estimation of antibody titers before the first dose and 4–6 weeks after the third dose of vaccination. Safety of each vaccine was assessed and compared by collection of data on solicited and unsolicited adverse events throughout the study period. Results: Out of a total of 405 enrolled subjects, 387 subjects completed the study. The seroconversion rates, seroprotection rates and geometric mean titres of the Investigational liquid Pentavalent (DTwP-Hb-Hib) combination vaccine group were found to be comparable and non-inferior to the Pentavac SD® vaccine group at 4–6 weeks after the third dose of vaccination. Pain, erythema and swelling at the site of injection were found to be the most common local adverse events whereas fever, irritability and unusual crying were found to be the most common systemic adverse events in both the vaccine groups. No vaccine related serious adverse event was reported. In this study, both the Investigational vaccine as well as the Comparator vaccine were found to be immunogenic and well tolerated. Conclusion: After assessment of the results of the study it was concluded that the Investigational liquid Pentavalent (DTwP-Hb-Hib) combination vaccine developed by Human Biologicals Institute was immunogenic and safe when administered to infants aged 6–8 weeks and was non-inferior in immunogenicity and safety to Pentavac SD® vaccine. Clinical Trial Registry of India Identifier: CTRI/2016/01/006541 .